Pelatihan Pembukuan Sederhana Berbasis Microsoft Excel Pada Usaha Mikro Kecil dan Menengah (UMKM) Kota Semarang - Andhy Tri Adriyanto; Wyati Saddewisasi; Agus Prasetyo (Jurnal Pengabdian kepada Masyarakat Radisi, 2023)
Making simple financial reports based on Microsoft Excel for managing business processes for the world of micro, small and medium industries is urgently needed for modernization in the field of bookkeeping, especially during the current Covid 19 pandemic. A bookkeeping system based on Microsoft Excel that is simple and easy to understand has now been created with the aim of assisting micro, small and medium enterprise (MSMEs) actors in obtaining business reports that are efficient, fast and accurate. The problem that arises is that the UMKM business actors are not accustomed to using a Microsoft Excel-based bookkeeping system, which makes the performance of the MSME business actors not good. Therefore, time and space are needed to improve the ability of MSME entrepreneurs in Semarang City to use a Microsoft Excel-based bookkeeping system to manage their business reports. The purpose of managing this bookkeeping system is that the system can improve the business performance of small, micro and medium enterprise (MSMEs) actors, especially in the city of Semarang. Increasing the ability of MSME business actors will be accommodated through the Community Service program using practical methods. MSME actors in the City of Semarang as training participants have received skills improvement training in using a simple bookkeeping system.